Noninvasive risk stratification of intraductal papillary mucinous neoplasia with malignant potential by serum apolipoprotein-A2-isoforms - Felix, Klaus M.; Honda, Kazufumi; Nagashima, Kengo; Kashiro, Ayumi; Takeuchi, Keiko; Kobayashi, Takashi; Hinterkopf, Sascha; Gaida, Matthias; Dang, Hien; Brindl, Niall; Kaiser, Jörg; Büchler, Markus W.; et al. (International journal of cancer, 2022)
Intraductal papillary mucinous neoplasms (IPMNs) are premalignant lesions of pancreatic cancer. An accurate serum biomarker, which allows earlier identification of asymptomatic individuals with high-risk for developing cancer, is of urgent need. Apolipoprotein A2-isoforms (apoA2-i) have previously been identified as biomarkers in pancreatic cancer. This study investigates a potential clinical application of the serum apoA2-i for risk stratification of IPMN and associated cancer. The concentrations of apoA2-i were retrospectively determined in 523 patient sera specimen, composed of 305 IPMNs with preinvasive lesions with different grades of dysplasia and invasive cancer, 140 pancreatic ductal adenocarcinoma, 78 with other cystic lesions and healthy controls cohorts, using an apoA2-i enzyme-linked immunosorbent assay kit. The diagnostic performance of serum apoA2-i was assessed and compared to routine clinical marker CA 19-9. ApoA2-i levels were significantly reduced in all IPMN samples regardless of stage compared to healthy controls. Receiver operating characteristic curve analysis of IPMNs with high-grade dysplasia and IPMN with associated carcinoma revealed the area under curve (AUC) of 0.91 and >0.94, respectively. The respective sensitivities were 70% and 83% with a specificity of 95%, and significantly higher than the gold standard biomarker CA 19-9. AUC values of apoA2-i for detecting IPMN-associated carcinoma of colloid and ductal subtypes were 0.990 and 0.885, respectively. ApoA2-i has the potential to early detect the risk of malignancy of patients with IPMN. The serological apoA2-i test in combination with imaging modalities could help improve the diagnosis of IPMN malignancy. Further validation in larger and independent international cohort studies is needed.